Situated design methods (The MIT Press, 2014)
All design is situated -- carried out from an embedded position. Design involves many participants and encompasses a range of interactions and interdependencies among designers, designs, design methods, and users. Design is also multidisciplinary, extending beyond the traditional design professions into such domains as health, culture, education, and transportation. This book presents eighteen situated design methods, offering cases and analyses of projects that range from designing interactive installations, urban spaces, and environmental systems to understanding customer experiences. Each chapter presents a different method, combining theoretical, methodological, and empirical discussions with accounts of actual experiences. The book describes methods for defining and organizing a design project, organizing collaborative processes, creating aesthetic experiences, and incorporating sustainability into processes and projects. The diverse and multidisciplinary methods presented include a problem- and project-based approach to design studies; a "Wheel of Rituals" intended to promote creativity; a pragmatist method for situated experience design that derives from empirical studies of film production and performance design; and ways to transfer design methods in a situated manner. The book will be an important resource for researchers, students, and practitioners of interdisciplinary design.
Keywords: Industrial design.; elektronické knihy; electronic books